PENGARUH ASSOCIATIVE PLAY TERHADAP TINGKAT STRESS PADA ANAK USIA 3-5 TAHUN - Ines Ratni Pravitasari; Didien Ika Setyaraini; Reni Wahyu Triningsih (Politeknik Kesehatan Kemenkes Malang, 2019)
The Phenomenon of fear more experienced by the child during pre-school than any other time.Continual fear will cause stress. This study aims to determine the effect of associative play on stresslevels in children aged 3-5 years. The methods used was quasy-experimental design with one grup pretest post test approach. Large sample is 25 students who experience stress. The research instrument wasthe School Anxiety Scale-Teacher Report (SAS-TR) questionnaire sheet. The results showed the stresslevel of children aged 3-5 years before associative play, namely the majority of respondents (52%)experienced moderate stress and after associative play experienced mild stress (60%). The results of thestudy were analyzed using the Wilcoxon Signed Rank Test with dan = 0.05 and showed the value of rvalue = 0,000 so that r value < H0, then H0 was rejected which means that there was an associative playeffect on stress levels in children aged 3-5 years.